First insight into the drug resistance pattern of Mycobacterium tuberculosis in Dohuk, Iraq: Using spoligotyping and MIRU-VNTR to characterize multidrug resistant strains - Muayad A. Merza; Parissa Farnia; Ahmad M. Salih; Mohammad Reza Masjedi; Ali Akbar Velayati (Elsevier, 2011)
Summary: The objectives of this study were to determine drug resistance pattern in new and previously treated tuberculosis (TB) patients, to assess function of TB control program, and to characterize multidrug resistant TB (MDR-TB) by molecular fingerprinting methods. Anti-micorbial susceptibility testing (AST) to the first line anti-TB drugs was performed on Löwenstein-Jensen (middlebrook 7H10) medium according to the proportion method. Molecular fingerprinting of all MDR strains was performed by spoligotyping and MIRU-VNTR. Mycobacterium tuberculosis strains were isolated from 53 Iraqi patients with pulmonary TB. Thirty eight patients (71.7%) tested cases, and 15 (28.3%) were previously treated. Four of the 38 new cases (10.5%) had resistant, of which 3 (7.9%) were MDR. Eight (53.3%) of the 15 previously treated patients had resistant strains, of which 7 (46.7%) were MDR. Spoligotyping of MDR strains showed CAS family (40%) as the predominant genotype. Using MIRU-VNTR typing, all isolates had a unique profile. MDR-TB prevalence is higher among previously treated patients than among the new cases. The many drug resistant strains, in absence of evidence of recent transmission and in combination with the many previously treated cases, highlight the need for an improved control program, coupled with a need to improve detection rate and early diagnosis of MDR-TB. Keywords: Tuberculosis, Multidrug resistant, Iraq, Drug susceptibility testing, Molecular genotyping